Study of the effect of added bronchoscopic suction to routine treatment of ventilator associated pneumonia patients in surgical ICU - Seyyed Hasan Karbasy; Maryam Bayati; Amir Sabertanha; Aram Meshkini; Bibi Fatemeh Shakhs Emampour (Journal of the Pakistan Medical Association, 2021)
Objective: Comparing BAL and antibiotic therapy with antibiotic therapy itself for treating VAP patients in ICU. Methods: In this randomized clinical trial. The first group was treated using antibiotics and closed-suction was performed daily, using 50 cc of sterile normal saline. The second group was treated with antibiotics and daily closed-suction with 50 cc of sterile normal saline, plus bronchoscopic suction every other day. Patients of both groups were followed and investigated one, 3, 7, and 10 days after initial diagnosis. Results: Mean blood leukocyte count and body temperature was measured in groups one (no bronchoscopy) and two (with bronchoscopy) in first, 3rd, 7th, and 10th days which was higher in the second group. Mean treatment status was also measured using APACHE II index. There was also a statistically significant difference in 3rd day (p-value < 0.05). There was also no difference in final culture result or mortality rate between two groups. Conclusion: According to the results of this study like lower body temperature, higher leukocyte count reduction, and lower APACHE II scores in the second group, treated with bronchoscopic suction, adding bronchoscopy seems to be more useful than normal method. Keywords: Bronchoscopy, Pneumonia, VAP, Continuous...